2022
DOI: 10.3389/fpsyg.2021.822588
|View full text |Cite
|
Sign up to set email alerts
|

Toward the Role of L2 Enjoyment in EFL Students' Academic Motivation and Engagement

Abstract: Since students' academic success is tied to their academic motivation and engagement, determining the predictors of these two variables seems critical. So, several inquiries have inspected the role of students' emotional and personal variables in their academic motivation and engagement. Nonetheless, the function of L2 enjoyment as an important emotional factor has remained elusive. Moreover, no inquiry has reviewed this issue neither systematically nor theoretically. To fill these lacunas, this review study a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 75 publications
1
10
0
Order By: Relevance
“…Enjoyment has received increasing scholarly attention along with the development of positive psychology (e.g., Pan and Zhang, 2021 ; Shen, 2021 ; Liu, 2022 ). Enjoyment is regarded as a component of flow, and it refers to a positive state in which challenges and the skills needed to deal with them are in line with each other ( Csikszentmihalyi, 1990 ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Enjoyment has received increasing scholarly attention along with the development of positive psychology (e.g., Pan and Zhang, 2021 ; Shen, 2021 ; Liu, 2022 ). Enjoyment is regarded as a component of flow, and it refers to a positive state in which challenges and the skills needed to deal with them are in line with each other ( Csikszentmihalyi, 1990 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…As the outcome of the interaction between both individual factors and the instructional context ( Baker et al, 2008 ), academic engagement is not only influenced by teacher-related factors such as teacher support and enthusiasm ( Dewaele and Li, 2021 ; Hejazi and Sadoughi, 2022 ) but also affected by students’ emotional and motivational variables ( Mystkowska-Wiertelak, 2020 ; Dewaele and Li, 2021 ). However, only sporadic studies have explored the relationship between engagement and students’ emotional variables and these limited studies indicated that positive emotions like enjoyment could promote students’ academic engagement (e.g., Guo, 2021 ; Liu, 2022 ), while negative emotions like boredom could make students disentangle from classroom learning activities (e.g., Dewaele and Li, 2021 ; Derakhshan et al, 2022b ). Further exploration is needed to better understand the influence of students’ achievement emotions on their engagement ( Derakhshan et al, 2022b ).…”
Section: Introductionmentioning
confidence: 99%
“…Enjoyment has been a great motivation for primary school students studying the English language and their second language [11]. Enjoyment as a motivation makes primary school students view English learning, writing and speaking as fun and full of excitement which makes them want to speak and write in English thus motivating them to study the English language.…”
Section: Enjoymentmentioning
confidence: 99%
“…Enjoyment as a motivation makes primary school students view English learning, writing and speaking as fun and full of excitement which makes them want to speak and write in English thus motivating them to study the English language. Enjoyment motivation arouses interest to learn the English language and this enables them to sustain their willingness to continue learning English even if they are facing challenges thus creating persistence in these students [11]. When the students enjoy the English language learning, they tend to be satisfied with the learning of the English language and they enjoy it or excite them.…”
Section: Enjoymentmentioning
confidence: 99%
“…This is why teachers in any instructional-learning environment constantly attempt to improve their students' classroom engagement. However, the ways in which students' academic engagement can be improved have remained unknown to a large group of teachers, including EFL teachers (Liu, 2021). Academic engagement, also known as classroom engagement, in a general sense refers to "the quality and quantity of students' participation or connection with the educational endeavor and hence with the activities, values, individuals, aims, and places that comprise it" (Skinner et al, 2009, p. 497).…”
Section: Introductionmentioning
confidence: 99%